Plastic fantastic? Problematising post-feminism in erotic retailing in England. Issue 10 (2nd October 2016) - Martin, Amber
Abstract: Sex shops in England have traditionally been perceived as masculinised consumption spaces, located at the margins of both the city and the clock (in decaying urban zones, hidden from view and frequented under the cover of darkness). Recent decades have witnessed the emergence of fashion conscious and female-orientated 'erotic boutiques', keen to disassociate themselves away from negative stereotypical representations of sex shops, through marketing themselves as stylish, fun, acceptable and safe, and, above all, empowering spaces for women to explore their sexuality. This article considers how erotic boutiques offer a post-feminist sexual address to women through claims of female empowerment, an embrace of traditional femininity and an endorsement of the aestheticisation of the female body. More specifically, I explore the post-feminist tensions between female sexual subjectivity and objectivity, by unpacking, and reflecting on, the relations between erotic boutiques and the space of the body. This is achieved by an analysis of how the products and services (and how they are marketed and displayed) promote idealised representations of female bodily sexual pleasure, adornment and knowledge that can apparently be obtained by the consumption of specific products and commodified sexual knowledges. The article consequently considers and questions a seeming inextricable entwinement of post-feminist sexual empowerment with sexual consumerism.